The evaluation of Fourier transform infrared (FT-IR) spectroscopy for quantitative and qualitative monitoring of alcoholic wine fermentation - Magerman, Cynthia M (Stellenbosch : Stellenbosch University, 2009)
Thesis (MSc (Wine Biotechnology))--Stellenbosch University, 2009.